POTENTIAL OF ROSELLA FLOWER EXTRACT KEFIR (HIBISCUS SABDARIFFA L.) IN REDUCING PANCREATIC β- CELL DAMAGE IN DIABETES MELLITUS MODEL RATS (RATTUS NORVEGICUS) - Anggi, Viani; Tandi, Joni; D, Rahmawati; M, Yulan; L, Wahyudin H (Universitas Muhammadiyah Magelang, 2025)
Kefir is a fermented milk product that contains probiotics, while rosella flowers (Hibiscus sabdariffa L.) are known to have antioxidant and antihyperglycemic activity. The combination of the two in the form of rosella flower extract kefir is expected to have a protective effect on the pancreas in diabetes. This study aims to evaluate the effect of administering rosella flower extract kefir preparations on the histopathological appearance of the pancreas of male white rats (Rattus norvegicus) induced by streptozotocin.This experimental study used a post-test control group design using 30 male white rats divided into several groups, namely normal controls who were given Na CMC 0.5% orally for 21 days, negative controls (induced by STZ without treatment) given Na CMC 0.5% orally for 21 days, positive controls (induced by STZ) and given glibenclamide suspension 0.45 mg/kg WB orally for 21 days, and treatment groups with different doses from kefir rosella flower extract with graded doses of 250 mg/kg BW, 500 mg/kg BW and 750 mg/kg BW. After treatment, rat pancreas was collected and analyzed histopathologically. The results of histopathological analysis showed that the group of mice that received rosella flower extract kefir at a dose of 750 mg/kg BW experienced structural improvements in pancreatic β cells with a damage value of 0.4. Administration of rosella flower extract kefir at a dose of 750 mg/kg BW has the potential to provide a protective effect on the pancreas in rats induced by streptozotocin